Employment equity discourses and practices of empowerment and identity in a bank - Canham, Hugo M (My University, 2014)
Since it began recording statistics on “race”, gender and disability in 2000, the Employment Equity Commission has criticised the appointment patterns of the private sector. In this regard, their data suggest that private sector organisations are generally employing black people, women, and people with disabilities into professional, senior, and top management roles, at a very slow pace. This research took this factor as a starting place to begin to explore issues beyond the numbers but which may in part account for the very slow pace of recorded change. The research explored employment equity discourses and practices of empowerment and identity in a bank. Focusing on the headquarters of one major bank in Johannesburg, 55 managers were interviewed using in-depth semi-structured interviews. Sixteen participants submitted written personal reflections on a collection of extracts that they were asked to read and respond to. A discussion group of black participants was conducted. Publicly available documents on the organisations demographic profile were analysed. Lastly, nine naturalistic observation sessions were conducted to get a sense of social patterns of engagement across “race” and gender. These data sets were explored using a qualitative framework and critical discourse analysis to make meaning of the data. The findings suggest that discourses of merit have become pervasive and cast doubt on the competence of black professionals and managers. More senior professionals and managers believe that they are substantively empowered while those with less authoritative power see themselves as relatively less empowered – these patterns were largely “race” based. Women primarily identified as raced (black or white) and white female participants distanced themselves from employment equity whereas black female participants bore the stereotypes associated with employment equity. Patterns of social engagement indicate marked voluntary self-segregation by “race” and micro segregation patterns. This suggested little career advancement opportunities for those groups with less organisationally powerful social networks. Lastly, employment equity discourses and practices were key constituting factors in identity constructions of the sample of bank managers that were studied.